Democratic process in Pakistan: causes of failure and development - Nandmehar, Sarita (JIPSINDO, 2025)
Pakistan's strategic significance in the global arena, especially in the aftermath of the September 11 attacks, stands in stark contrast to the ongoing political turbulence that has characterised the nation for decades. The intricate political landscape is primarily influenced by entrenched military and bureaucratic forces, overshadowing the aspirations for genuine democratic governance. This dynamic has led to a climate of persistent unrest, where the struggle between democratic ideals and authoritarian practices manifests in numerous ways. Historically, Pakistan has experienced a tumultuous back-and-forth between democracy and authoritarianism, resulting in a fragmented political structure that coups and the frequent replacement of leadership have marred. These disruptions have led to a lack of cohesive political consensus, a disregard for constitutional principles, and ineffective electoral mechanisms—all of which have severely undermined the foundations of democracy in the country. The military's intervention in politics has been a recurring theme, with significant coups occurring in 1958, 1969, 1977, and 1999. Each of these episodes ushered in periods of military rule that, while sometimes resulting in short-term economic growth and a semblance of political unity, paradoxically bred deeper authoritarian tendencies and stifled democratic progress. As a result, the nation has struggled with fragmented political factions and escalating violence, which now pose significant threats to its stability. These issues reflect the deep-rooted challenges within Pakistan's political system, making it a complex and often unstable landscape.